Comparison of time and frequency domain features' immunity against lift-off in pulse-compression eddy current imaging. (October 2019) - Ferrigno, Luigi; Laracca, Marco; Malekmohammadi, Hamed; Tian, Gui Yun; Ricci, Marco
Abstract: This paper reports a comparison between imaging procedures based on time- and frequency-domain features applied to eddy current data collected on an Aluminium alloy benchmark sample. Both the defect detection capability and the immunity against lift-off are analysed. Historically, the pulsed eddy current method was introduced to improve the performance of eddy current testing both in terms of increased penetration depth and lift-off invariance by exploiting time-domain features analysis, commonly precluded when using single- or multi-tone excitations. In this work, such analysis is instead accomplished by using a swept-frequency excitation signal along with an optimized pulse-compression procedure. This approach allows the user to easily tune the energy delivered to the system by increasing the sweep duration to improve on demand the resultant Signal-to-Noise Ratio (SNR) without losing the capability of time-domain feature extraction. The imaging procedure makes use of amplitude and phase features of both frequency- and time-domain data where time-phase is defined through the Hilbert transform of the pulse-compression output. The detection capability of various imaging strategies, namely A-, B- and C-scans, are compared in terms of inspection depth and lift-off robustness by using the SNR merit factor. It is shown that time-domain features outperform frequency-based ones in terms of SNR for the case of deeper defects and that phase features are robust against lift-off variations for both time and frequency domains. In addition, the analysis of time-amplitude images clearly shows the presence of lift-off invariant points. To our knowledge, this is the first experimental evidence of the lift-off invariance points retrieved after applying pulse-compression in combination with coded excitation instead of using directly pulsed, multi-tone or single-tone sinusoidal signals. This not only confirms previous results achieved by the authors but also demonstrates that pulse-compression eddy current can represent a solution to combine the advantages of pulsed and sinusoidal excitation strategies.